Role of Pyroptosis in Inflammatory Bowel Disease (IBD): From Gasdermins to DAMPs - Zhang, Shuxia; Liang, Yujie; Yao, Jun; Li, De-feng; Wang, Li-sheng (Frontiers in Pharmacology, 2022)
Pyroptosis is a pro-inflammatory cell death executed by gasdermin family proteins that involves the formation of pores on cells, recognition of danger signals and release of pro-inflammatory cytokines IL-1β and IL-18. Pyroptosis modulates mucosal innate immunity and enteropathogenic bacterial infection. while, Similarly, the Gasdermin family has been reported to be involved in the defense of the intestinal epithelium against bacterial infection and in the regulation of intestinal inflammation. Pyroptosis initiates damage signals that activate multiple pathways to cause inflammation, which may be a potential cause of chronic intestinal inflammation. In this review, we discuss the impact of pyroptosis on inflammatory bowel disease (IBD), with a focus on the executive proteins of pyroptosis (GSDMB, GADMD, and GSDME) and IBD-related endogenous damage-associated molecular patterns (DAMPs) produced by pyroptosis.